A dual conducting network corbelled hydrated vanadium pentoxide cathode for high-rate aqueous zinc-ion batteries. Issue 3 (6th January 2022) - Xu, Yu-Ting; Chen, Meng-Jie; Wang, Hong-Rui; Zhou, Chun-Jiao; Ma, Qiang; Deng, Qi; Wu, Xiong-Wei; Zeng, Xian-Xiang
Abstract : A vanadium pentoxide with structural water molecules as a pillar to expand layer spacing was grown on a carbon and polymer dual conductive network and realized rapid charge mass transportation for high-rate and energy-dense zinc-ion batteries. Abstract : Aqueous zinc-ion batteries (ZIBs) are widely recognized for their excellent safety and high theoretical capacity but are hindered by the scarcity of cathode materials with high-rate performance and stability. Herein, a dual conducting network corbelled hydrated vanadium pentoxide that involves structural water as a pillar to enlarge the layer spacing of vanadium pentoxide and ensure cycling stability was reported. Along with the proton co-insertion, the hydrated vanadium pentoxide delivers nearly theoretical specific capacities of 524.6 mA h g −1 at 0.3 A g −1 and 258.7 mA h g −1 at 10 A g −1, which was largely due to non-faradaic contribution, and retains 196.8 mA h g −1 at 4.8 A g −1 after 1100 cycles. Notably, a high energy density of 409.3 W h kg −1 at 0.3 A g −1 and a power density of 6666.4 W kg −1 at 10 A g −1 have also been achieved. The design strategy offers a potential path to develop high-rate ZIBs.